Helminthic infections mimicking malignancy: a review of published case reports - Pilsczek, Florian H. (The Journal of Infection in Developing Countries, 2010)
Background: Infectious diseases, including infections with helminths, can initially present similarly to malignancies. The goal of the article is to review reports of helminthic infections that are initially diagnosed as malignancy. Methodology: The database PubMed was searched for English language references published as of July 2009. Results: The following published case reports and case series, mainly from Asia and Africa, were identified: Nematodes: 8 publications (1 patient with Angiostrongylus cantonensis, 2 Stronglyloides stercoralis, 1 Toxocara species, 1 Dioctophyma renale, 1 Ascaris species, 1 Gnathostoma spinigerum, 1 Dirofilaria repens); Trematodes: 7 publications (46 patients with Schistosoma species, 2 Fasciola hepatica, 1 Paragonimus westermani); Cestodes: 6 publications (10 patients with Echinococcus species, 1 Sparganum mansoni). Conclusion: To avoid unnecessary investigations and treatment, physicians should be aware when diagnosing patients from Asia or Africa that a large number of helminthic infections can present similar to malignancies.